分解因式(x+y+z)的平方减(x-y-z)的平方

2025-02-28 04:28:20
推荐回答(5个)
回答1:

(x+y+z)的平方-(x-y-z)的平方
=(x+y+z+x-y-z)(x+y+z-x+y+z)
=2x(2y+2z)
=4x(y+z)
祝学习进步,望采纳~~

回答2:

解:原式=[(x+y+z)+(x-y-z)][(x+y=z)-(x-y-z)]
=(x+y+z+x-y-z)(x+y+z-x+y+z)
=2x*(2y+2z)
=4x(y+z)

回答3:

利用平方差公式,得
=[(x+y+z)+(x-y-z)][(x+y+z)-(x-y-z)]
=(x+y+z+x-y-z)(x+y+z-x+y+z)
=2x(2y+2z)
=4x(y+z)

回答4:

原式=(x y z x-y-z)(x y z-x y z)
=2x(2y 2z)
=4x(y z)
不懂请追问!
PS:空白处为加号!

回答5:

x+y+z)^2-(x-y-z)^2 =[(x+y+z)+(x-y-z) ][(x+y+z)-(x-y-z) ] =(x+y+z+x-y-z)(x+y+z-x+y+z) =(2x)*(2y+2z) =4x(y+z)